New means and new methods of research: challenges, solutions and advances - Batista, Leandro Leonardo; Perez, Clotilde (Organicom, 2016)
The present article debates the evolution of the new media and their languages, mainly in the digital sphere, and their impact on market research methods and techniques. The question is discussed from two fundamental research segments: coverage and responses, considering the new challenges brought by digitalised life, as well as the advances and improvements in the planning, execution and analysis of the researches. In the end, it discusses the ethical issues concerning the theme and the limitations inherent to the reflection presented.